Do local ao global: o processo de reestruturação na Volkswagem/Anchieta entre 2001 e 2006 - Arruda, Lilian Rose (2010)
This thesis discusses the processes of productive restructuring at Volkswagen/Anchieta initiated between 2001 and 2006 by the German headquarters, which were implemented in this company but faced a context of union purposeful practice, also called negotiated restructuring, led by the ABC Metalworkers' Union. In addition to conflicts between business and union representatives, members of the Workers' Committee of Volkswagen/Anchieta also faced internal disagreements with members of the opposition to the leadership of the ABC Metalworkers' Union. It should be remembered that these processes occurred in the contemporary historical context marked by globalization. Companies adopt global strategies regarding the processes of productive restructuring, but these processes, in this case, object of our thesis, have different configurations because of national government policies and the regional performance of the union and workers movement where that company is located. One goal of this thesis is to analyze the negotiations between management and employees representatives during the process of productive restructuring at Volkswagen/Anchieta, between 2001 and 2006, from the speeches enunciated by several social actors including members of the Volkswagen Global Group Works Council (GGWC) about the action proposal. From this perspective, union purposeful practice comprises negotiation and conflict resolution